(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2024)
This study explores the linguistic challenges faced by Hausa native speakers when learning Arabic, focusing on phonetics, morphology, grammar, and semantics. Situated within the framework of Arabic language acquisition, particularly for Hausa speakers from northern Nigeria and neighbouring regions, the research identifies distinct hurdles such as the unique phonetic systems of Arabic, encompassing pharyngeal and emphatic consonants, which differ significantly from Hausa. The contrastive approach is pivotal in highlighting these differences, with an emphasis on systematic sound progression from simpler to more complex articulations to enhance phonetic accuracy. Morphologically, Arabic’s complex derivational and inflectional patterns pose difficulties compared to Hausa’s simpler structure, requiring integrated teaching strategies that elucidate Arabic’s grammatical intricacies. Semantically, Hausa learners grapple with the expansive Arabic lexicon and its nuanced meanings, necessitating the selection of high-frequency words presented progressively in meaningful contexts. This study advocates for tailored educational approaches that integrate cultural understanding and extracurricular activities to enhance Arabic language proficiency among Hausa speakers. By addressing these challenges through enhanced instructional methods and materials, educators can effectively support Hausa learners in mastering Arabic language skills.